THE ROLE OF SYAMIL AND DODO CARTOON FILMS TO FOSTER LEARNING MOTIVATION IN IMPROVING STUDENT LEARNING OUTCOMES SUBJECTS OF MORAL BELIEFS - Muhammad Afif Agistiannur; Muhammad Ramli (International Journal of Multidisciplinary Reseach, 2025)
Learning motivation is the encouragement of students to achieve learning goals, such as understanding the material. In the learning of Akidah Akhlak Class IV MI Al Hidayah, the cartoon films of Syamil and Dodo are used to help students understand material such as honesty and trust. This film provides a direct and concrete explanation so that it makes it easier for students to understand. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results of the study showed that: (1) After watching the film Syamil and Dodo, students seemed more motivated in learning. They show enthusiasm, curiosity, pay close attention to impressions, and actively work on assignments. (2) The students' response to this film was very positive because it made it easier for them to understand the subject matter. (3) No significant obstacles were found in understanding the message of the film, because the content of the film is easy to understand by teachers and students. The obstacle faced is that students forget the time if learning starts using the film media of Syamil and Dodo and when the film screening is interrupted due to a power outage.